Primary Amyloidosis of Larynx A Case Report (Bangladesh Journal of Otorhinolaryngology, 2015)
Amyloidosis is an idiopathic benign disorder in which extracellular proteinaceous material deposits in variety of organs leading to tissue damage and functional problem of that organ. Besides larynx being the commonest site, amyloidosis is found in other head neck sites such as salivary glands, oral cavity, pharynx, nasopharynx, sinonasal cavity, trachea, bronchi, lungs & lymph node. This is a report of a 40 year old man admitted in the departement of Otolaryngology-Head and Neck Surgery, BSMMU, Dhaka, Bangladesh, in 2014, presented with history of hoarseness of voice and polypoidal swelling involving left vocal cord, ventricle and vestibular fold. Initially he was treated with antitubercular chemotherapy as direct laryngoscopic biopsy reported tuberculosis. As symptoms did not subside repeat direct endoscopic biopsy was done when histopathological examination confirmed the diagnosis of amyloidosis. MRI shows transglottic involvement of lesion which appears more extensive than endoscopic findings. Regular follow-up is necessary to assess accurately the disease progression, using conservative clinical management to preserve laryngeal function. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22026 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 98-101